Polymorphonuclear Cells Show Features of Dysfunctional Activation During Fatal Sepsis - Hortová-Kohoutková, Marcela; De Zuani, Marco; Lázničková, Petra; Bendíčková, Kamila; Mrkva, Ondřej; Andrejčinová, Ivana; Mýtniková, Alexandra; Polanský, Ondřej; Kočí, Kamila; Tomášková, Veronika; Šrámek, Vladimír; Helán, Martin; et al. (Frontiers in Immunology, 2021)
Sepsis and septic shock remain leading causes of morbidity and mortality for patients in the intensive care unit. During the early phase, immune cells produce various cytokines leading to prompt activation of the immune system. Polymorphonuclear leukocytes (PMNs) respond to different signals producing inflammatory factors and executing their antimicrobial mechanisms, resulting in the engulfment and elimination of invading pathogens. However, excessive activation caused by various inflammatory signals produced during sepsis progression can lead to the alteration of PMN signaling and subsequent defects in their functionality. Here, we analyzed samples from 34 patients in septic shock, focusing on PMNs gene expression and proteome changes associated with septic shock. We revealed that, compared to those patients who survived longer than five days, PMNs from patients who had fulminant sepsis were characterized by a dysfunctional hyper-activation, show altered metabolism, and recent exit from the cell cycle and signs of cellular lifespan. We believe that this multi-omics approach, although limited, pinpoints the alterations in PMNs’ functionality, which may be rescued by targeted treatments.